ADAPTED ALGORITHM OF VIRTUAL PLANTS SIMULATION BASED ON STOCHASTIC L-SYSTEM - Wang, Hai; Hao, Fei (International Journal of Computing, 2010)
In this paper, the concept and characteristics of fractal are briefly introduced; The drawing principle of L-system and IFS system is discussed. Based on this discussion, we analyse virtual plant growth procedure simulated by the L-system. Further, an efficient expression that can describe the plant growth and the control of direction is defined; Inspired from proposed expression, we propose a new method based on the combination of L-system and IFS system to simulate the plant morphology. We valid and show our proposed system with high fidelity and efficiency on the simulation of plant morphology by comparison experiments. Extra experiment shows it can be applied into computer art and video game scenario design.